2009
DOI: 10.1128/jcm.00854-09
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Susceptibility of Aspergillus Isolates Recovered from Patients Enrolled in the Transplant-Associated Infection Surveillance Network

Abstract: We analyzed antifungal susceptibilities of 274 clinical Aspergillus isolates from transplant recipients with proven or probable invasive aspergillosis collected as part of the Transplant-Associated Infection Surveillance Network (TRANSNET) and examined the relationship between MIC and mortality at 6 or 12 weeks. Antifungal susceptibility testing was performed by the Clinical and Laboratory Standards Institute (CLSI) M38-A2 broth dilution method for amphotericin B (AMB), itraconazole (ITR), voriconazole (VOR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
95
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(113 citation statements)
references
References 29 publications
15
95
1
2
Order By: Relevance
“…These observations suggest that A. calidoustus conidia remain dormant and may be able to cause significant tissue invasion/ destruction only in the presence of severe and sustained immunosuppression. This is consistent with successful animal models of experimental invasive aspergillosis by Aspergillus fumigatus which have been achieved by frequent administration of at least two agents to obtain and maintain profound and persistent immunosuppression mimicking human invasive aspergillosis (9)(10)(11)(12).…”
supporting
confidence: 57%
“…These observations suggest that A. calidoustus conidia remain dormant and may be able to cause significant tissue invasion/ destruction only in the presence of severe and sustained immunosuppression. This is consistent with successful animal models of experimental invasive aspergillosis by Aspergillus fumigatus which have been achieved by frequent administration of at least two agents to obtain and maintain profound and persistent immunosuppression mimicking human invasive aspergillosis (9)(10)(11)(12).…”
supporting
confidence: 57%
“…to itraconazole, posaconazole, and voriconazole as determined by both methods. The MIC results for each agent were typical of those for each species of Aspergillus (1,9,17,19,22,28).…”
mentioning
confidence: 83%
“…Each of these agents has good in vitro and in vivo activity against most species of Aspergillus (1,9,12,16,17,22,29). Although resistance (R) to triazoles is uncommon, increased R has been noted in several regions of the world since 1999 (11,12,23,25,27,28).…”
mentioning
confidence: 99%
“…Similarly, the population-based FILPOP survey to investigate the epidemiology and antifungal resistance in Spanish clinical strains of filamentous fungi from deep-tissue samples, blood cultures, and respiratory samples reported that 12% of the isolates were cryptic Aspergillus species (9). The most notable findings in both studies were that the cryptic species had high in vitro MICs to multiple antifungal drugs, including azoles and amphotericin B (9,10). Both azoles and amphotericin B antifungals are agents of choice to treat Aspergillus infections; thus, high MICs to these agents pose a serious therapeutic challenge.…”
mentioning
confidence: 84%